El agrohidronegocio en la región chaqueña argentina (Salta, Santiago del Estero y Córdoba) - Toledo-López, Virginia Belén; Schmidt, Mariana Andrea; Ayrala Quiroga, Marina (Pontificia Universidad Católica del Perú, 2023)
In Argentina, the provinces of Córdoba, Salta and Santiago del Estero are cases of great importance in the context of agribusiness expansion, due to the spectacular loss of biodiversity, the frequent territorial conflicts carried out by indigenous peoples and peasants and, more recently, against the use of agrochemicals and their consequences on human and non-human health. This article aims to make visible some of the emerging experiences in the territories under study as transition initiatives, with special emphasis on the construction of resistances and alternatives.To this end, we address the main irruptions of agribusiness in the Chaco's web of life (understood as agrohydrobusiness, given the centrality assumed by the dispute over water resources in this region), considering its territorial, environmental and health consequences, to then analyze the main forms assumed by resistances and re-existences. The methodological proposal focuses on simultaneous work with different information construction and analysis techniques, such as: systematization and analysis of multiple secondary sources (journalists, statistics, legislation, reports from state and/or private organizations, among others), along with field records and in-depth interviews.

En Argentina las provincias de Córdoba, Salta y Santiago del Estero se constituyen en casos de gran significancia en el contexto del avance del agronegocio, en virtud de la enorme pérdida de biodiversidad, la recurrente conflictividad territorial protagonizada por pueblos indígenas y campesinos y, más recientemente, contra el uso de agrotóxicos y sus consecuencias en la salud humana y no humana. El artículo se propone poner de relieve la dimensión hídrica involucrada en el modelo de agricultura hegemónico y visibilizar la construcción de alternativas que emergen en los territorios bajo estudio. A tal fin, abordamos las principales irrupciones del agrohidronegocio en la trama de la vida chaqueña, atendiendo a sus consecuencias territoriales, ambientales y sanitarias; para luego detenernos en un análisis de las principales formas que asumen las resistencias y las re-existencias. La propuesta metodológica se centra en un trabajo simultáneo con distintas técnicas de construcción y procesamiento de la información, tales como: sistematización y análisis de múltiples fuentes secundarias (periodísticas, estadísticas, legislaciones, informes de organismos estatales y/o privados, entre otras), junto con registros de campo y entrevistas en profundidad.
Agrohydrobusiness in the Chaco Region of Argentina (Salta, Santiago del Estero and Córdoba)
Keywords: Agrohydrobusiness; Dry Chaco; Resistances; Re-existences; Alternatives; Agrohidronegocio; Chaco seco; Resistencias; Re-existencias; Transiciones; https://purl.org/pe-repo/ocde/ford#5.04.00